Heterotrimeric G proteins control stem cell proliferation through CLAVATA signaling in Arabidopsis. (August 2016) - Ishida, Takashi; Tabata, Ryo; Yamada, Masashi; Aida, Mitsuhiro; Mitsumasu, Kanako; Fujiwara, Masayuki; Yamaguchi, Katsushi; Shigenobu, Shuji; Higuchi, Masayuki; Tsuji, Hiroyuki; Shimamoto, Ko; Hasebe, Mitsuyasu; et al.
Abstract :